The role of nongovernmental organizations in the empowerment of Syrian refugee women in Turkey - Bulut, Aybala. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This study examines the role of nongovernmental organizations in eliminating political, social, economic, and gender-based obstacles in the way of ensuring empowerment for Syrian refugee women who fled the Syrian Civil War and settled in Turkey in the past ten years. The rapid influx of refugees paralyzed the Turkish migration management system. Millions of refugees settled in urban areas despite precarious conditions. Not being granted official refugee status by the Turkish state, the temporary protection regime made it difficult for Syrians to enjoy fundamental human rights. Civil society had to step up, playing the role of intermediaries between refugees and the state while providing humanitarian aid of all sorts. This qualitative research formulated upon several semi-structured, in-depth interviews conducted with NGOs operating in the field examines how the gender-based disadvantage experienced by refugee women has been addressed in NGOs' agendas and what strategies are developed in order to push decision makers to have a gender perspective. Our study shows that these NGOs have shed light on the gender-blindness of traditional state apparatus and pushed their mechanisms to acknowledge the multiple disadvantages experienced by refugee women. NGOs discovered alternative ways for refugee women to access the necessary social capital for empowerment. Despite the political pressure upon civil society, NGOs introduced a more gender-based conceptualization of social cohesion and integration by empowering refugee women and aiming to impact various decision-making mechanisms.
Keywords: Refugees, Syrian -- Women.; Refugees, Syrian -- Turkey.; Syria -- History -- Civil War, 2011-